A nestling-sized skeleton of Edmontosaurus (Ornithischia, Hadrosauridae) from the Hell Creek Formation of northeastern Montana, U.S.A., with an analysis of ontogenetic limb allometry. Issue 6 (2nd November 2017) - Wosik, Mateusz; Goodwin, Mark B.; Evans, David C.
ABSTRACT: The Hell Creek Formation preserves one of the most intensely studied late Cretaceous terrestrial fossil units. Over 22 dinosaur genera are currently recognized from this unit, but the record of juvenile individuals is surprisingly limited. Here, we document a nestling hadrosaur that represents the first occurrence of an articulated nestling dinosaur skeleton from the latest Cretaceous (late Maastrichtian) of North America. The specimen (UCMP 128181) preserves a partial scapula, nearly complete rib cage, vertebral series from the shoulder to mid-tail, a large portion of the pelvic girdle, and both hind limbs through a combination of bone and/or natural impressions in the concretion. It is assignable to the genus Edmontosaurus based on the shape of the prepubic process, or blade, of the pubis. The specimen represents the earliest ontogenetic growth stage of Edmontosaurus cf. annectens and possesses a femur length of 148 mm. It greatly contributes as a new end member to a sample of associated Edmontosaurus skeletons that is well suited for allometrically testing the hypothesized ontogenetic gait shift in hadrosaurs from bipedal juveniles to quadrupedal adults using individual limb proportions. Although UCMP 128181 does not preserve forelimbs, regressions based on associated Edmontosaurus skeletons (N = 25) reveal overall isometry of the forelimb relative to the hind limb, and within each limb. These data indicate that Edmontosaurus nestlings were anatomically capable of fully quadrupedal locomotion and provide no compelling evidence to support an ontogenetic gait shift in hadrosaurids. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Wosik, M., M. B. Goodwin, and D. C. Evans. 2018. A nestling-sized skeleton of Edmontosaurus (Ornithischia, Hadrosauridae) from the Hell Creek Formation of northeastern Montana, U.S.A., with an analysis of ontogenetic limb allometry. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1398168.